The red devil battery sign - Williams, Tennessee 1911-1983 (A New Directions book, 1988)
This book is William's symbol for the military-industrial complex and all the dehumanizing trends it represents from mindless cocktail party chatter to bribery of officials to assassination plots directed against those who won't play the game, to attempted coups by right-wing zealots.